Load Testing and In-service Monitoring of Transversely Stressed Deck Unit Bridges - N.S. Ngo; T. Pape; R.P. Kotze; R.W. Pritchard (Electronic Journal of Structural Engineering, 2015)
Transversely stressed precast concrete deck unit bridges are a common type of small and medium span bridge on the Queensland road network. This type of bridge is unique in design featuring transverse posttensioned stressing bars with a low level of prestressing, stiff upright kerb units and no shear keys. Recent structural assessments of these bridge types has yielded varied and at times inconsistent results, with theoretical structural deficiencies identified at odds with the lack of evidence of structural distress, demonstrating acceptable performance. A test program was developed to address this disparity and improve understanding of the structural performance of these bridge types. This included static and dynamic load testing with various vehicle types, and long-term monitoring of the behaviour of a representative bridge under ambient traffic. The test results have enabled improved understanding of the behaviour and true capacity of this bridge type, as well as providing inputs to enable validation of analytical structural modelling techniques.